Factores asociados al grado de satisfacción del usuario del consultorio externo de gastroenterología del Hospital Central de la Fuerza Aérea del Perú. Mayo, 2014 - La Torre Mantilla, Angello Rafael (2018)
ABSTRACT An observational, descriptive and cross-sectional study was performed to determine the factors associated with the degree of user satisfaction at the outpatient Gastroenterology Service in the Air Force´s Central Hospital from Peru, because the patient’s insatisfaction is associated to the level of professional excellence, the efficient use of resources and very low risk for the patient. The sample consisted of 221 ​​patients. It was found that 21.3 % patients were satisfied with the care provided, 26.7 % in the reliability component, 31.2 % in the liability component, 48 % in the security component, 38.9 % in the empathy component and 32.6 % in the tangible component. Insatisfaction was observed in 75 (70.8 %) of males, 99 (86.1 %) of females (p = 0.005), 65 (70.7 %) of direct beneficiaries and 109 (84.5 %) of the family members (p = 0.013). Also, as the waiting time for care increased patient´s satisfaction decreased (r = -0.316, p = 0.000). RESUMO Desenvolveu-se um estudo observacional, descritivo e transversal para determinar os fatores associados ao grau de satisfação do utente da clínica médica ambulatória de gastrenterologia do Hospital Central da Força Aérea de Peru, devido a que a insatisfação do paciente é associada com o nível de excelência profissional, uso eficiente dos recursos e mínimo risco para o paciente. A amostra incluiu 221 pacientes. Achou-se que 21.3 % de pacientes estavam satisfeitos com o atendimento, 26,7 % com o componente fiabilidade, 31.2 % no componente responsabilidade, 48 % no componente segurança, 38.9 % no componente empatia e 32.6 % com no componente tangíveis. A insatisfação observou-se em 75 (70.8 %) dos homens, 99 (86.1 %) das mulheres (p = 0.005), 65 (70.7 %) dos beneficiários direitos e 109 (84.5 %) dos parentes (p = 0.013). Além disso, à medida que aumentava o tempo de espera para o atendimento, diminuía a satisfação do paciente (r = -0.316; p = 0.000).